Metabolic Profile of Downer Cow syndrome - Mhachuvino Catherine Khatsu (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 1994)
The metabolic profile of ‘Downer Cow’ syndrome in field conditions was studied. Fourteen field cases of ‘Downers’ in crossbred dairy cows aged three to thirteen years, ranging from 250 to 300 kg body weight from Trichur district were selected at random and utilized for the study. Fourteen apparently healthy crossbred dairy cows of similar age group and body weight, maintained under similar conditions of feeding and management from the area from which the clinical cases studied were also selected at random and utilized as the healthy controls. Samples of blood for haematological and biochemical parameters, urine and dung from both healthy and diseased animals were collected and analysed using standard methods. Analyses of the data from fourteen diseased animals indicated a higher incidence in Jersey crossbred cows during summer season. Prominent clinical signs were sternal recumbency exhibiting hindquarter weakness and reduced feed and water intake. However, the affected animals remained bright and alert with no evidence of any systemic disturbances. The clinical data were within physiological limit. Highly significant increase in PCV and significant increase in Hb but no significant difference in ESR, RBC and WBC were observed. Lymphopenia, neutrophilia and eosinopenia were observed with no variation in basophils and monocytes counts. Biochemically, hypocalcaemia,hypophosphataemia, hypoproteinaemia and hypoalbuminaemia were obtained from ‘Downers’ with no significant variation in blood glucose, urea nitrogen, sodium, potassium, magnesium and albumin/globulin ratio. Urinalysis revealed no consistent result indicative of any systemic involvement and no parasitism on dung examination microscopically.